Intelligent Approach Based on Group Method of Data Handling to Predict Economic Growth Through Entrepreneurship and Innovativeness with Time Series - ŞENVAR, ÖZLEM (My University, 2022)
© 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.Entrepreneurship and innovativeness are the key factors for determination of economic viability along with preservation of sustainability. Entrepreneurship with innovation is a crucial part of economic improvement and growth and substantial for the steady dynamism of the modern economy. Since entrepreneurship and innovation generate value for the economy through creative destruction, their impacts on GDP growth (annual %) can be examined through anticipatory capacities. Brexit is expected to have serious consequences of generating international entrepreneurship and business opportunities for companies worldwide. This study aims to anticipate economic growth through entrepreneurial activities and innovativeness before and after the Brexit decision. In this study, New Business Density and R&D Expenditure (% of GDP) are handled to make anticipations regarding annual GDP Growth (%) via time series forecasting algorithm. We consider Iceland, Ireland and the UK before and after Brexit decision. Iceland and Ireland are taken into account due to their close relationships with the UK.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Sinyal İşleme; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Control and System Engineering; Signal Processing; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; OTOMASYON & KONTROL SİSTEMLERİ; TELEKOMÜNİKASYON; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; Engineering, Computing & Technology (ENG); ENGINEERING; AUTOMATION & CONTROL SYSTEMS; TELECOMMUNICATIONS; ENGINEERING, ELECTRICAL & ELECTRONIC; Fizik Bilimleri; Bilgisayar Ağları ve İletişim; Control and Systems Engineering; Physical Sciences; Computer Networks and Communications; Entrepreneurship; Innovativeness; Economic growth; Anticipation; Group Method of Data Handling (GMDH); Entrepreneurship; Innovativeness; Economic growth; Anticipation; Group Method of Data Handling (GMDH)